Perceived Financial Preparedness for Retirement of Technical Teachers : An Empirical Study in Andhra Pradesh, India - Voleti, Kiran Kumar; Kumar, Pawan; Nanda, Sudhansu Sekhar; Debata, Bikash Ranjan (Prabandhan: Indian Journal of Management, 2024)
Purpose : Technical teachers are relatively more financially vulnerable due to local government intervention in determining the fee structure in technical colleges. This research set out to answer the question, â€œHow financially prepared are these teachers in Andhra Pradesh, India, for retirement?â€ by examining the variables and their correlations. Methodology : A self-administered, online, structured survey was conducted among technical education teachers. The survey was distributed through various online platforms, and 384 usable responses were obtained. The questionnaire used in the study was adopted based on the content analysis of issues in the relevant literature. Structural equation modeling was employed for the analysis. Findings : Financial knowledge and future time perspective were found to have a significant impact on perceived financial preparedness. Financial risk tolerance, a commonly identified factor in literature, was not statistically significant for this study. Practical Implications : The findings of this study were not just insightful but also urgent. They provided a clear roadmap for policymakers and researchers to develop targeted interventions and strategies. These interventions enhanced retirement planning and financial well-being among technical education teachers. By understanding the factors that influence financial preparedness, we could design effective retirement planning programs tailored to the needs of this specific population. Originality : This study is a unique and novel contribution to the literature. It focused on the financial preparedness for retirement, specifically among technical education teachers in Andhra Pradesh, India. This study significantly enhanced our understanding of retirement planning behaviors in diverse socio-cultural settings by addressing a gap in the existing literature and examining retirement concerns and preparedness in a non-Western context.